Le Canada, ou, Partie de la Nouvelle France, contenant la Terre de Labrador la Nouvelle France, les isles de Terre Neuve, de Nostre Dame, &c. - Mortier, Pierre (Amsterdam)
Hand coloured. Two compass roses with rhumb lines. Relief shown pictorially. Bar scales in Italian miles, French common leagues, German common leagues, English common miles, "lieues d'une heure de chemin," and common sea leagues. Includes notes. CNS map no. 119.